2002
DOI: 10.1364/ao.41.005804
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved studies of the interactions between pulsed lasers and aerosols

Abstract: Studies of the interaction between a pulsed CO2 laser and micrometer-sized aqueous and organic particles by use of light-scattering methods and step-scan Fourier-transform infrared (FTIR) spectroscopy are reported. Visible two-color extinction experiments indicate primary particle shattering, accompanied by a high fraction of vaporization, followed by secondary particle evaporation. The extent of the latter depends on the pulse intensity and particle composition. Angle-resolved light-scattering investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Previous reports on aerosols have focused on the associated heat and mass transfer processes that occur regarding their influence on the atmosphere when aerosols are heated with a source of light such as lasers. [19][20][21][22] Heating an aerosol with a laser beam induces temperature gradients in the fluid surrounding the particle, causing a change in the index of refraction of the fluid in the vicinity of the particle. The amount of energy an aerosol absorbs from the incident light beam depends on the complex index of refraction of the particle as well as on its optical size (where the optical size x is given by x ¼ 2pr/k, where r and k are the particle radius and laser wavelength, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports on aerosols have focused on the associated heat and mass transfer processes that occur regarding their influence on the atmosphere when aerosols are heated with a source of light such as lasers. [19][20][21][22] Heating an aerosol with a laser beam induces temperature gradients in the fluid surrounding the particle, causing a change in the index of refraction of the fluid in the vicinity of the particle. The amount of energy an aerosol absorbs from the incident light beam depends on the complex index of refraction of the particle as well as on its optical size (where the optical size x is given by x ¼ 2pr/k, where r and k are the particle radius and laser wavelength, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The diameter D p = 2 mm of the mixture particles is assumed to comply with the measurements [10], where the emission of fine droplets with the size of 2 mm is observed during the interaction of short laser pulses with water or soft biological tissues. The experimental study of aerosol with micron-size water droplets [17] has shown that the droplet diameter decrease of 10% occurs only after $20 ms even in case of higher energy laser pulses. Since the particle diameter is assumed unaltered in-flight, the extinction factor Q ext (l) and K ext (l) are constant over the simulation time.…”
Section: Model Of Plume-laser Interactionmentioning
confidence: 99%
“…C 2 H 2 or C 2 HD scattered off LiF surfaces [35,40]). The diffusion-cell experiments on aerosols also paved the way for Miller to establish an extensive collaboration on time-of-flight mass spectrometry of laserirradiated aerosols with Tomas Baer and coworkers [222][223][224][225][226][227][228][229][230][231][232][233][234].…”
Section: Acetylene As a Mechanistic Probe: Part Of The Miller Legacymentioning
confidence: 99%